INFLUENCE OF WAVE MOTION OF FLUID SURFACE ON BEHAVIOR OF SPHERICAL PARTICLES - Bochkarev G.P.; Izotov A.S.; Kondrat'ev S.A. (My University, 2001)
Behavior of the floating metallic spherical particles has been considered. Action of the standing capillary wave on them has been observed. The particles sink under action of the wave. Mathematical model of movement of the spherical particles on the wavy fluid surface has been developed. Shift of perimeter of three-phase contact has been taken into account in the model. Removal of the particle from gas-fluid interface occurs in case of certain wave. Amplitude of the wave have been calculated with the use of the model. The amplitude has been also measured in experiment. Results of the calculation agree with experimental data.